Systematic review and quantitative meta-analysis of age-dependent human T-lymphocyte homeostasis - Kulesh, Victoria; Peskov, Kirill; Helmlinger, Gabriel; Bocharov, Gennady (Frontiers in Immunology, 2025)
ObjectiveTo evaluate and quantitatively describe age-dependent homeostasis for a broad range of total T-cells and specific T-lymphocyte subpopulations in healthy human subjects.MethodsA systematic literature review was performed to identify and collect relevant quantitative information on T-lymphocyte counts in human blood and various organs. Both individual subject and grouped (aggregated) data on T-lymphocyte observations in absolute and relative values were digitized and curated; cell phenotypes, gating strategies for flow cytometry analyses, organs from which observations were obtained, subjects’ number and age were also systematically inventoried. Age-dependent homeostasis of each T-lymphocyte subpopulation was evaluated via a weighted average calculation within pre-specified age intervals, using a piece-wise equal-effect meta-analysis methodology.ResultsIn total, 124 studies comprising 11722 unique observations from healthy subjects encompassing 20 different T-lymphocyte subpopulations – total CD45+ and CD3+ lymphocytes, as well as specific CD4+ and CD8+ naïve, recent thymic emigrants, activated, effector and various subpopulations of memory T-lymphocytes (total-memory, central-memory, effector-memory, resident-memory) – were systematically collected and included in the final database for a comprehensive analysis. Blood counts of most T-lymphocyte subpopulations demonstrate a decline with age, with a pronounced decrease within the first 10 years of life. Conversely, memory T-lymphocytes display a tendency to increase in older age groups, particularly after ~50 years of age. Notably, an increase in T-lymphocyte numbers is observed in neonates and infants (0 – 1 year of age) towards less differentiated T-lymphocyte subpopulations, while an increase into more differentiated subpopulations emerges later (1 – 5 years of age).ConclusionA comprehensive systematic review and meta-analysis of T-lymphocyte age-dependent homeostasis in healthy humans was performed, to evaluate immune T-cell profiles as a function of age and to characterize generalized estimates of T-lymphocyte counts across age groups. Our study introduces a quantitative description of the fundamental parameters characterizing the maintenance and evolution of T-cell subsets with age, based on a comprehensive integration of available organ-specific and systems-level flow cytometry datasets. Overall, it provides the most up-to-date view of physiological T-cell dynamics and its variance and may be used as a consistent reference for gaining further mechanistic understanding of the human immune status in health and disease.